Cultural diversity and the Zimbabwean pungwe as carnival space : a comparison with the Brazilian carnivalesque experience - Viriri, Advice (Unisa Publications, 2016)
The article critically examines the influence and effects of Africa's double tragedy and very momentous incidents of slavery and colonialism to the Caribbean people of African descent. In spite of all the cultural emasculations, the denigrations of slaves by their slave masters in this present day age and low esteem with which Africans and Caribbeans of African descent are regarded in world opinion, they were able to cling on to their African cultural elements. To the Caribbean person of African descent it was worse off than the African person because of having undergone a double process of enslavement and colonization. This article has chosen to compare the Brazilian carnivalesque celebrations to show the retention of firmer linkages with the African cultures particularly with the Zimbabwean Pungwe as offering carnival space during and after the Chimurenga War.